Affective Practices, Care and Bioscience: A Study of Two Laboratories. Issue 1 (February 2016) - Kerr, Anne; Garforth, Lisa
Scientific knowledge-making is not just a matter of experiments, modelling and fieldwork. It also involves affective, embodied and material practices (Wetherell, 2012 ) which can be understood together as 'matters of care' (Puig de la Bellacasa, 2011 ). In this paper we explore how affect spans and connects material, subjective and organizational practices, focusing in particular on the patterns of care we encountered in an observational study of two bioscience laboratories. We explore the preferred emotional subjectivities of each lab and their relation to material practice. We go on to consider flows and clots in the circulation of affect and their relation to care through an exploration of belonging and humour in the labs. We show how being a successful scientist or group of researchers involves a careful choreography of affect in relation to materials, colleagues and others to produce scientific results, subjects and workplaces. We end by considering how thinking with care troubles dominant constructions of scientific practice, successful scientific selves and collectives.